Disease progression in Parkinson's disease patients with subjective cognitive complaint. Issue 10 (30th September 2021) - Han, Lin‐Lin; Wang, Lan; Xu, Zhi‐Heng; Liang, Xiao‐Niu; Zhang, Meng‐Wei; Fan, Yun; Sun, Yi‐Min; Liu, Feng‐Tao; Yu, Wen‐Bo; Tang, Yi‐Lin
Abstract: Objective: Little is known about the disease progression of Parkinson's disease patients with subjective cognitive complaint (PD‐SCC). This longitudinal cohort study aims to compare the progression of clinical features and quality of life (QoL) in PD patients with normal cognition (NC), SCC, and mild cognitive impairment (MCI). Methods: A total of 383 PD patients were enrolled, including 189 PD‐NC patients, 59 PD‐SCC patients, and 135 PD‐MCI patients, with 1–7 years of follow‐up. Linear mixed models were applied to evaluate longitudinal changes in motor symptoms, nonmotor features (cognitive impairment, depression, and excessive daytime sleepiness), and QoL in PD. Results: At baseline, PD‐SCC patients had lower Beck Depression Inventory (BDI) scores and Parkinson's Disease Questionnaire‐39 (PDQ‐39) scores than PD‐NC patients (all p < 0.05). Longitudinal analyses revealed that the PD‐SCC group exhibited faster progression in terms of BDI scores ( p = 0.042) and PDQ‐39 scores ( p = 0.035) than the PD‐NC group. The PD‐MCI group exhibited faster progression rates in the Epworth Sleepiness Scale scores ( p = 0.001) and PDQ‐39 scores ( p = 0.005) than the PD‐NC group. In addition, the PD‐SCC group exhibited a greater reduction in attention (Trail Making Test Part A, p = 0.047) and executive function (Stroop Color‐Word Test, p = 0.037) than the PD‐NC group. Interpretation: PD‐SCC patients exhibited faster deterioration of depression and QoL than PD‐NC patients, and SCC may be an indicator of initial attention and executive function decline in PD. Our findings provided a more accurate prognosis in PD‐SCC patients.